PERAN DINAS LINGKUNGAN HIDUP KOTA DUMAI DALAM PENCEGAHAN ABRASI PANTAI DI KELURAHAN MUNDAM KECAMATAN MEDANG KAMPAI KOTA DUMAI TAHUN 2020 - Syarif, Muhamad Aryudi; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia has the second longest coastline in the world after Canada, with great potential for coastal abrasion. One of the areas that has the potential for abrasion is Dumai City, which is geographically located on the east coast of Sumatra. For this reason, regulations in the form of clear authority are needed to prevent these problems. The purpose of this research is to find out the authority delegated to the Regency / City Government in taking care of its coastal and marine areas after changes in previously established regulations and to see the role of the Dumai City Environment Office in preventing coastal abrasion in Mundam Village, Medang Kampai District, Dumai City in 2020. This research method uses a qualitative approach with descriptive research type. The research location is in Dumai City, to be precise at the Dumai City Environmental Agency, the Dumai City DPRD and Mundam Village which is the area that is the most location point of abrasion in Dumai City in 2020. The type of data in this study is divided into primary data with purpsive sampling technique and secondary data in the form of supporting documents related to coastal abrasion in Dumai City. The result of this research is that the existence of regulatory changes has an impact on the limited authority of the Regency / City Government in managing its coastal and marine areas, especially in abrasion prevention efforts, where the authority is fully given to the provincial government. For this reason, the Dumai City Environment Agency can only carry out the authority of assistance tasks delegated from the provincial government in the form of monitoring the quality of the coastal and marine environment, and the Covid-19 outbreak in 2020 has an impact on the programs carried out in abrasion prevention efforts. This makes coastal abrasion still occur in Dumai City and Mundam Village is the location of the most abrasion in 2020. Keyword : Authority, Role, Environment Agency of Dumai City, Beach Abrasion